EXPERIENCE IN THE MANAGEMENT OF BORDERLINE OVARIAN TUMORS - Miranda Flores, Alan Francis (2025)
Introduction. Borderline ovarian tumors are epithelial neoplasms of low malignant potential, commonly found in young women. They have a favorable prognosis and, in selected cases, allow for conservative surgical treatment. Objectives. To describe the experience in the management of borderline ovarian tumors at a level III 2 healthcare facility in Lima, Peru. Methods. Descriptive, cross-sectional, and retrospective study. Eight patients with confirmed diagnoses were included, treated between 2020 and 2022. Results. The mean age was 53.1 years. The most frequent histologic subtype was serous (62.5%). The average tumor size was 17.8 cm, and the mean CA-125 level was 52.6 U/mL. Most tumors (75.0%) were unilateral and diagnosed at early stages. The most common treatments were complete staging and unilateral adnexectomy (25.0% each). Conclusion. Borderline ovarian tumors have a favorable clinical course. Conservative surgery is a safe option for young women with reproductive desire.